Clinical improvement in a patient with severe coronavirus disease 2019 after administration of hydroxychloroquine and continuous hemodiafiltlation with nafamostat mesylate. Issue 12 (December 2020) - Iwasaka, Sho; Shono, Yuji; Tokuda, Kentaro; Nakashima, Kosuke; Yamamoto, Yuzo; Maki, Jun; Nagasaki, Yoji; Shimono, Nobuyuki; Akahoshi, Tomohiko; Taguchi, Tomoaki
Abstract: The number of people infected with severe acute respiratory syndrome coronavirus 2 is increasing globally, and some patients have a fatal clinical course. In light of this situation, the World Health Organization (WHO) declared coronavirus disease 2019 (COVID-19) a pandemic on March 11, 2020. While clinical studies and basic research on a treatment for COVID-19 are ongoing around the world, no treatment has yet been proven to be effective. Several clinical studies have demonstrated the efficacy of chloroquine phosphate and nafamostat mesylate with COVID-19. Here, we report the case of a Japanese patient with COVID-19 with severe respiratory failure who improved following the administration of hydroxychloroquine and continuous hemodiafiltlation with nafamostat mesylate. Hence, hydroxychloroquine with nafamostat mesylate might be a treatment option for severe COVID-19.